SUPEROVULATORY RESPONSE IN SAHIWAL x JERSEY CROSSBRED COWS WITH DIFFERENT DOSES OF FSHp - REDDY, Y V PRIDHVIDHAR; VEERABRAMHAIAH, K; KRISHNA, K MOULI; REDDY, Y RAVINDRA (The Indian Journal of Animal Reproduction, 2015)
Sahiwal x Jersey crossbred cows were superovulated with 250 and 200 mg FSHp from d10 to 13 of PGF2α synchronized estrous cycle in divided doses and luteolysis on 72h after initiation of superovulatory treatment. All donors responded to superovulatory treatment and the mean ovulation rate, embryo recovery rate and anovulated follicles in 250 mg and 200 mg FSHp group were 4.67±0.33 and 3.50±0.34 (p<0.05); 2.33±0.33 and 2.00±0.26 and 3.17±0.17 and 2.00±0.45 (p<0.05), respectively. In brief, the superovulatory response was more in donor cows with 250 mg than 200 mg of FSHp.